Comparison of selected biological parameters of laboratory susceptible and field collected strains of the. German cockroach, lattella germanica (L.) (Dictyoptera: Blattellidae) - Yang Lee, Chow-; Heng Yap, Han-; Long Chong, Ngo- (Malaysian Journal of Science, 1996)
Selected biological parameters of five field collected strains (GoldenSand, Melia I, Kuantan, Lumut and Subang) of the German cockroach, Blattella germanica (L.) in Peninsular MalayÂsia, were compared with that of the laboratory susceptible strain (ICI). All field strains demonstrated longer nymphal development, preoviposition and incubation period, lower fecundity and shorter longevity than the ICI strain. The GoldenSand strain had a lower intrinsic rate of increase (re) than the ICI strain, but Melia I showed a comparable rn value to that of the susceptible strain.